EPOKSIDASI MINYAK JARAK JATROPHA CURCAS L. UNTUK MENINGKATKAN STABILITAS DAN PERFORMA PELUMAS NABATI RAMAH LINGKUNGAN - Agus Dwi Putra; Farida, Nike Nur; Monasari, Ratna; Rakhmaddian, Nicko Nur; Fadhilah, Intan; Prasetyo, Heru (Universitas Islam Malang, 2025)
The decline of petroleum reserves and environmental issues from petroleum-based lubricants have driven interest in biolubricants. Jatropha curcas L. oil is a promising candidate due to its availability and non-edible nature, but it lacks sufficient oxidative stability and thermal performance. This study aims to improve jatropha oil quality through in situ epoxidation. The research included oil extraction, initial chemical analysis (acid value, moisture, saponification value, iodine value), epoxidation with varied reactant ratios and reaction times, and post-modification tests of viscosity and flash point. Results indicated that oil yield from dehulled seeds was higher (60%) than hulled seeds (25%). Epoxidation improved viscosity from 2.39 cSt to 34.2 cSt at 40°C and raised the flash point from 109°C to 270°C. These enhancements demonstrate improved physicochemical properties, making epoxidized jatropha oil a potential eco-friendly lubricant comparable to modern synthetic lubricants.